A measurement method for lossy capacitive relative humidity sensors based on a direct sensor-to-microcontroller interface circuit. (January 2021) - Czaja, Zbigniew
Graphical abstract: Highlights: A new time-domain measurement method for lossy capacitive sensors is proposed. An interface circuit consists of only two (or four) reference resistors and a sensor. The method is for microcontrollers with internal analog comparators and timers. An error correction algorithm based on the correction dictionary is proposed. Relative errors <0.71% for capacitance and <0.74% for resistance measurements. Abstract: A new time-domain measurement method for determining the capacitance and resistance values of lossy relative humidity capacitive sensors is presented. The method is based on a direct sensor-to-microcontroller interface for microcontrollers with internal analog comparators and timers. The interface circuit consists only of four reference resistors (two reference resistors if a microcontroller includes a voltage reference source), a given sensor and a microcontroller. A systematic error correction algorithm based on a correction dictionary and the M -multiple measurement approach are also proposed in the paper. Experimental investigations were carried out using a prototype device based on an 8-bit ATXmega32A4 microcontroller. The experimental research confirmed that the relative errors of measurement of capacitance introduced by the interface circuit are less than 0.71% (for capacitance values 100–286 pF), and the relative errors of measurement of resistance are less than 0.74% (for resistance values 1–10 MΩ).